Carrier Status of Leptospirosis Among Cattle in Sri Lanka: A Zoonotic Threat to Public Health. Issue 1 (24th September 2012) - Gamage, C. D.; Koizumi, N.; Perera, A. K. C.; Muto, M.; Nwafor‐Okoli, C.; Ranasinghe, S.; Kularatne, S. A. M.; Rajapakse, R. P. V. J.; Kanda, K.; Lee, R. B.; Obayashi, Y.; Ohnishi, M.; et al.
Summary Leptospirosis is a zoonotic disease of global importance and one of the notifiable diseases in Sri Lanka. Recent studies on human leptospirosis have suggested that the cattle could be one of the important reservoirs for human infection in the country. However, there is a dearth of local information on bovine leptospirosis, including its implications for human transmission. Thus, this study attempted to determine the carrier status of pathogenic Leptospira spp in cattle in Sri Lanka. A total of 164 cattle kidney samples were collected from the meat inspection hall in Colombo city during routine inspection procedures conducted by the municipal veterinary surgeons. The DNA was extracted and subjected to nested PCR for the detection of leptospiral flaB gene. Amplicons were sequenced, and phylogenic distances were calculated. Of 164 samples, 20 (12.2%) were positive for flaB‐PCR. Sequenced amplicons revealed that Leptospira species were deduced to L. borgpetersenii (10/20, 50%), L. kirschneri (7/20, 35%) and L. interrogans (3/20, 15%). The results indicate that a high proportion of the sampled cattle harbour a variety of pathogenic Leptospira spp, which can serve as important reservoirs for human disease.